Youth participation in holticulture and poverty reduction in rural areas: A case study of horticultural production in Mvomero District, Tanzania - Nyalulu Gulamiwa, George (Mzumbe University, 2023)
A Dissertation Submitted to the Institute of Development Studies in Partial Fulfillment of the Requirements for the Award of Master Degree in Development Policy (MSc DP) of Mzumbe University.